A double jeopardy: COVID-19 impacts on the travel behavior and community living of people with disabilities. (February 2022) - Park, Keunhyun; Chamberlain, Brent; Song, Ziqi; Nasr Esfahani, Hossein; Sheen, Jeff; Larsen, Teresa; Long Novack, Valerie; Licon, Carlos; Christensen, Keith
Highlights: Respondents reduced daily travel significantly during COVID-19. Reductions in taxi (Uber/Lyft) trips were most significant among those with disabilities. Reductions in trips to grocery stores and community services were most significant among those with disabilities. Cognitive disability was associated with a trip reduction for multiple destination types. Abstract: The COVID-19 pandemic response has had a significant impact on the general population's ability to participate in their communities. Individuals with disabilities, an already socially disadvantaged population, are more vulnerable to and have likely been disproportionately impacted by COVID-19 response conditions. Yet, the extent to which the daily community living activities of people with disabilities have been impacted is unknown. Thus, this study assesses their travel behavior and community living during the COVID-19 pandemic conditions compared with those of the general population. A web survey was conducted using Qualtrics's online panel data (respondents included 161 people with any type of disability and 232 people without a disability). Regression models found that people with disabilities reduced their daily travel to a greater extent but at varying degrees, depending on the destination types and travel modes. Reductions in taxi rides (including ride-hailing services) were most significant among people with cognitive and sensory (e.g., vision and hearing) disabilities. By place type, cognitive disability was associated with a trip reduction for multiple destination types—grocery, restaurants, outdoor recreation, indoor recreation, and healthcare providers. Findings from this study could contribute to decision- and policy-making in planning, transportation, and community services during the remainder of the COVID-19 pandemic, in future major public health crises, and post-COVID, because the adjustments in travel behavior and community living might be longer-term.